Youth in System of Implementation of Policy of State and Social Control in USSR (1927-1929) - A. A. Slezin; V. A. Ippolitov (Научный диалог, 2019)
The article studies the experience of the organization of youth associations created to implement the functions of social and state control in the USSR. It is shown that in the late 1920s, the youth movement has developed from a few groups of Komsomol control to the mass participation of boys and girls in the implementation of control functions. The authors focus on the participation of young people in the sections of the Worker-Peasant Inspection and creation of “light cavalry” units, which directed their activities to rationalize the work of state institutions, prompt consideration of complaints of the population, self-identification of shortcomings. The basic forms of organizational structure of youth control units, the causes of organizational difficulties at the initial stage of their operation are revealed. Having made a conclusion about expediency of inclusion of youth in activity on improvement of public administration, the authors nevertheless note that already at the initial stage of activity of “light cavalry” in the organizational sphere opposite tendencies were shown: development of self-government and work pro bono was opposed by bureaucracy of the Komsomol asset duplicating the negative moments in style of work of mentors from party-state apparatus. The materials of the Russian State Archive of Social and Political History are widely used in the study, the evidence of contemporaries is involved.